1988
DOI: 10.1677/joe.0.1160025
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotrophin and cyclic AMP regulation of thyroglobulin gene expression in cultured porcine thyroid cells

Abstract: The effects of thyrotrophin, cholera toxin and 8-chloro-cyclic AMP on thyroglobulin gene expression in cultured porcine thyroid cells were compared. Cells organized either into monolayers in culture chambers with porous bases or into inside-out follicles in suspension were used. Thyroglobulin mRNA content was measured by dot-blot hybridization, and thyroglobulin synthesis rate was determined by immunoprecipitation of [35S]thyroglobulin after 2 h labelling with [35S]methionine. Cholera toxin and 8-chloro-cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Expression of the Tg and TPO genes is restricted to thyroid tissue (4) and is under hormonal control. The pituitary hormone TSH, via cAMP, insulin, and insulinlike growth factor I (IGF-I) exerts a positive effect on Tg (5)(6)(7)(8)(9) and TPO (10 -14) gene expression. The hormonal regulation mechanism of Tg and TPO promoter activities has been studied extensively in the last few years, since their promoters are well characterized (15,16).…”
mentioning
confidence: 99%
“…Expression of the Tg and TPO genes is restricted to thyroid tissue (4) and is under hormonal control. The pituitary hormone TSH, via cAMP, insulin, and insulinlike growth factor I (IGF-I) exerts a positive effect on Tg (5)(6)(7)(8)(9) and TPO (10 -14) gene expression. The hormonal regulation mechanism of Tg and TPO promoter activities has been studied extensively in the last few years, since their promoters are well characterized (15,16).…”
mentioning
confidence: 99%
“…A significant effect of iodide on the specific radioactivity appeared only in the presence of TSH:+TSH+KI/+TSH-KI=1.4. Different stages of thyroglobulin expression have been studied for their dependence on TSH, and the maximal responses were not obtained with the same concentration of hormone for each process (26). The usual concentration of TSH in that culture system was 100 mU/ml, added to the basolateral side of the cells; at this concentration all the effects of TSH reached a plateau.…”
Section: Regulation Of the Incorporation Of Sulfate Residues Into Thymentioning
confidence: 99%
“…Over many years, we have accumulated extensive data on this culture system, which simulates thyroid metabolism in vivo, up to the stage of secretion of thyroid hormones into the basal medium (unpublished results). We have shown that TSH controlled all the steps of thyroglobulin metabolism that we have studied: thyroglobulin expression and secretion (25)(26)(27)(28), and two post-translational modifications, glycosylation (29,30) and iodination (31).…”
Section: Introductionmentioning
confidence: 99%
“…Total cellular RNA was isolated as previously described (Chabaud et al, 1988). The amount of total cellular RNA was determined in each assay by absorbance at 260 nm (Eo.…”
Section: Rna Isolation and Quantificationmentioning
confidence: 99%
“…Tg mRNA content was determined from dot-hybridization assays (Chabaud et al, 1988). Briefly, a precisely measured amount (10-20-pg range) of cellular RNA from each assay was incubated a t 50°C for 30 min in a 2 0 4 glyoxal-dimethylsulfoxide (DMSO) mixture as described by Tosta et al (1983).…”
Section: Rna Isolation and Quantificationmentioning
confidence: 99%